Assessment of Water Quality Parameters and Their Correlations in the Kalimas River, Surabaya: Implications for Health Risks - Alfan KURNIANTO; Sarita OKTORINA; Ida MUNFARIDA; Diah Nugraheni SETYOWATI; Arqowi PRIBADI (International Journal of Environmental, Sustainability, and Social Science, 2024)
The Kalimas River, which flows through industrial and residential areas, faces significant pollution pressure due to diverse anthropogenic activities. This study evaluates the water quality parameters of the Kalimas River in Surabaya, Indonesia, and investigates the correlations among these parameters to assess potential health risks. Key parameters assessed include temperature, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), and total suspended solids (TSS). Sampling was conducted along ten strategically selected segments. The results reveal varying levels of pollution, with elevated BOD5, COD, and TSS values indicating organic and chemical pollution, and low DO levels signalling oxygen depletion in certain sections. Statistical analysis using Spearman’s correlation demonstrated significant relationships among variables, such as a negative correlation between temperature and DO. Health risks are evident, as high COD and BOD levels promote pathogen growth, increasing the risk of waterborne diseases, while elevated TSS may carry pollutants that further threaten public health. The presence of low DO levels also disrupts aquatic ecosystems, which can exacerbate bacterial growth, posing additional health hazards to communities using the river for daily activities. These findings highlight the need for urgent interventions to mitigate pollution and protect both ecological health and public safety.